The Role of Information sciences in shaping collaborative work practices: A sociological perspective on Organizational management - DR MUMTAZ BANO (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
With the fast pace of development of information technology on one hand and the growing density of the organizational environment on the other hand, the importance of information science to promote combined work patterns has become a necessity. The subject that will be discussed in this paper is how information sciences and sociology can be applied in organizational management specifically with regards to the role of information systems and technologies in enabling and supporting collaborative work and communication across multiple teams. From a sociological perspective, we analyze the interactions in communication processes mediated by digital technologies focusing on cultural and structural aspects of collaboration in organizations. Data gathered from these organizations also show that good practice of information management leads to improved team integration, productivity as well as innovation. Moreover, this study discovers that there are limits to collaboration, for example, technology acceptance and the differential technology proficiency among the employees. The implications are that organisations need to approach the issues from an information sciences as well as sociological perspective to design work as an integrated whole which is as it should be. Finally, this work advances the knowledge of how organizational management practices may benefit from information sciences to foster sustainable organizational change in the present-day workplaces.